Abandoned land, corporate farming, and farmland banks: a local perspective on the process of deregulating and redistributing farmland in Japan. Issue 1 (2nd January 2017) - Jentzsch, Hanno
ABSTRACT: This paper analyzes the policy process toward farmland consolidation and deregulation in Japan. The current Abe administration has introduced so-called Farmland Banks to facilitate land transfers to expanding farms, including general corporations, which have long been banned from farmland access in Japan. The paper argues that farmland deregulation puts the 'incumbent' local stakeholders of farmland governance, such as local agricultural cooperatives, local administrations, and not least farmers themselves, at risk of losing access to state support and influence. At the same time, the responsibilities for coordinating farmland consolidation have been placed onto the same local stakeholders. The state of local farmland governance has long been critical to impeding coordinated consolidation, whereas deregulation facilitates 'predatory' corporate farmland use. In contrast, evidence from Hikawa Town in Shimane Prefecture shows how exceptionally strong local control over farmland enables consolidation—albeit in the 'defensive' interests of the local incumbents.